Communication of School Heads in Improving Education Performance in SMA Plus Private Vocational School, Al-Azhar Medan - Samsuddin; Rusydi Ananda (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aims to explore the principal's communication in an effort to improve the performance of educators.This qualitative research is conducted in SMA Plus Swasta Al-Azhar Medan from January to April 2018 to the principal, vice principal of curriculum and teacher. Research instruments are researchers and assisted by interview guides, observation sheets and documentation studies. The validity of data is done by member checking process of transcript by direct respondent or supervisor. Analysis and interpretation of data with a qualitative pattern that refers to the theoretical basis associated with the studied. The results of the study found a top-down and bottom-up communication, briefing or training, meetings at the beginning of the year and scheduled meetings, the principal's behavioral obstinacy, as well as the funisment for oral and written offenses and rewards for those who show achievement. Increased communal harmony through shared recreation. The forms of headmaster communication that have been executed must be maintained for the improvement of subordinate performance.